Neurosurgery outlines - Kaloostian, Paul Edward, 1981- (Surgical outlines, 2020)
"Surgery requires a combination of knowledge and skill acquired through years of direct observation, mentorship, and practice. The learning curve can be steep, frustrating, and intimidating for many medical students and junior residents. Too often, books and texts that attempt to translate the art of surgery are far too comprehensive for this audience and counterproductive to learning important basic skills to succeed. Neurosurgery Outlines by neurosurgeon Paul Kaloostian is the neurosurgical volume in a series of textbooks that offer a simplified roadmap to surgery. This unique resource outlines key steps for common surgeries, laying a solid foundation of basic knowledge from which trainees can easily build and expand. The text serves as starting point for learning neurosurgical techniques, with room for adding notes, details, and pearls collected during the journey. Chapters are systematically organized and formatted by subspecialty, encompassing spine, radiosurgery, brain tumors and vascular lesions, head trauma, functional neurosurgery, epilepsy, pain, and hydrocephalus. Each chapter includes symptoms and signs, surgical pathology, diagnostic modalities, differential diagnosis, treatment options, indications for surgical intervention, step-by-step procedures, pitfalls, prognosis, and references where applicable"--